Historiografi Lokal Tragedi Desa Kolam 1965 dan Peran Barisan Tani Indonesia (BTI) dalam Konteks Sosial-Politik Sumatera Utara - Lilis Putri Simamora; Siti Julaiha; Marshal Gilbert Sinambela; Immanuel Steven Limbong; Elianti Napitupulu; Sry Yanti Barus (Local History & Heritage, 2025)
This study examines the local historiography of the 1965 tragedy in Desa Kolam and analyzes the role of Barisan Tani Indonesia (BTI) within the broader socio-political landscape of North Sumatra. Using a qualitative historical method that integrates archival analysis, oral histories, and field observation, the research reconstructs community-level experiences that are largely absent from national narratives of the G30S/PKI period. The findings show that Desa Kolam served as an operational base for BTI prior to the 1965 upheaval, became a site of targeted violence following the state’s designation of the PKI as a prohibited organization, and continues to grapple with collective memory shaped by trauma, silence, and contested interpretations of the past. The study concludes that the micro-history of Desa Kolam offers significant insights into the complexity of political violence in Indonesia and highlights the importance of community-rooted perspectives in enriching the broader historiography of 1965.